PELATIHAN PENGELOLAAN ADMINISTRASI DESA - Alrasyid, M Harun; Rofieq, Ainur; Supriyanto, Hasan (DEVOSI, 2021)
The village as the lowest government organizational structure becomes the frontline of services that directly come into contact with the community, therefore the ability and capacity of the village government apparatus plays a very important role. In order to create good village governance, the village government needs to be supported by proper village administration. The method used is in the form of training on village administration management. So that with this training, it is expected that government administration and financial governance, especially in increasing the capacity of human resources of village apparatus in realizing orderly village administration which functions as a source of data and information on village government administration, implementation of development, coaching, community, and community empowerment.